Ultrafast singlet fission and intersystem crossing in halogenated tetraazaperopyrenes - Wollscheid, Nikolaus; Günther, Benjamin; Rao, Vaishnavi J.; Berger, Felix J.; Pérez Lustres, José Luis; Motzkus, Marcus; Zaumseil, Jana; Gade, Lutz H.; Höfener, Sebastian; Buckup, Tiago (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2020)
Charge carrier multiplication via singlet fission into two triplet states has the potential to increase efficiencies of photovoltaics by one-third due to the reduction of thermalization losses. In the present work, we investigate tetraazaperopyrenes, a class of N-heteropolycyles, as suitable singlet fission candidates. Using a combined experimental and theoretical approach, fundamentally different mechanisms for triplet formation in solution and thin film are identified. In solution, an ultrafast intersystem crossing process is observed, which is accelerated for heavier halide substituents not only due to enhanced spin-orbit coupling but also due to the energy tuning between the S1 and T2 states. In thin films, a correlated triplet pair is formed coherently upon photoexcitation. Subsequently, an excimer formation is observed, which competes with the electronic decorrelation of the triplet pair. The comparison with peropyrene shows that aza-substitutions within the aromatic core can be a powerful strategy for tuning the energy levels of the states important to singlet fission.